$1!:P!_?!D&!4c!`cs - Unknown (Salt Lake City, UT : Project Gutenberg, 2016)
"$1!:P!_?!D&!4c!`c(B" by Unknown is a classic Chinese narrative poem written during the Han Dynasty, which falls within the broad time span of the early centuries AD. This work is a tragic love story that reflects themes of devotion, societal expectations, and familial loyalty. It is known for its poignant exploration of the consequences of love thwarted by external pressures. The poem centers on the tale of Jiao Zhongqing and his wife, Liu, who face immense pressure from their families regarding their marriage. Liu, loyal to her husband and unwilling to marry another, ultimately takes her own life, leading Zhongqing to follow suit in his grief. Their tragic deaths evoke a deep sense of sorrow from the community, culminating in a collective mourning that highlights the themes of love, fidelity, and despair. The poem$1 (Bs imagery and lyrical style convey the intensity of their emotions and the cultural significance of their story, marking it as a poignant commentary on the struggles between personal desires and societal obligations. (This is an automatically generated summary.)s
Release date is 2016-06-08
Produced by Huang Bing-Jun
Keywords: Chinese poetry -- Qin and Han dynasties, 221 B.C.-220 A.D.; Yue fu (Chinese poetry)